2012
DOI: 10.1002/ejoc.201200850
|View full text |Cite|
|
Sign up to set email alerts
|

First Intramolecular Alkylation of Nitriles with Primary and Secondary Alcohols Catalyzed by Iridium Complexes

Abstract: The first iridium‐catalyzed intramolecular alkylation ofnitriles with primary and secondary alcohols through hydrogen transfer is described. This reaction allows access to precursors of biologically active arylmethylamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Thereaction of 35 and 36 affords the hydroxy amide 37 which can be further converted into ac yclic imide by dehydrogenative formation of the hemiaminal 38 as apotential intermediate. [26] Vogt et al reported ruthenium catalyst systems,c omprising [Ru 3 (CO) 12 ]and CataCXiumPCy (40), for intramolecular cyclization of a,w-amino alcohols to afford the cyclic amines 41 as well as the cyclic amides 42 [Eq. (13)].…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereaction of 35 and 36 affords the hydroxy amide 37 which can be further converted into ac yclic imide by dehydrogenative formation of the hemiaminal 38 as apotential intermediate. [26] Vogt et al reported ruthenium catalyst systems,c omprising [Ru 3 (CO) 12 ]and CataCXiumPCy (40), for intramolecular cyclization of a,w-amino alcohols to afford the cyclic amines 41 as well as the cyclic amides 42 [Eq. (13)].…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
“…(24)]. [40] Iridium catalytic systems such as [{Cp*IrCl 2 } 2 ]a nd [{Ir(cod)Cl} 2 ]/PPh 3 were highly efficient catalysts under microwave conditions.Both catalytic systems showed similar reactivities and cis/trans selectivities for the construction of chromanes,w hereas [{Ir(cod)Cl} 2 ]/PPh 3 showed better yields for the synthesis of thiochromane-4-carbonitrile.T he reaction path consists of initial catalytic dehydrogenation of an alcohol to form acarbonyl compound and subsequent intramolecular condensation of the carbonyl with an active methylene group to provide olefin functionalities.F inally hydrogenation of the condensed product utilizing the borrowed hydrogen affords the corresponding O-and S-containing heterocyclic compounds 85.…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
“…Since 1981, when Grigg and co‐workers first used RuH 2 (PPh 3 ) 4 as a catalyst in the alkylation of nitriles with alcohol, a lot of effort has been devoted to exploring various catalysts, including Ru, Rh, Ir, Pd, Os, Fe, and Mn. Of these, Ru complexes are the most reported, for example Gunanathan's group reported that Ru(PNP) (PNP = bis(2‐(diphenylphosphino)‐ethyl)amine) pincer complex showed good activity for α ‐alkylated reaction of arylmethyl nitriles .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Later, alkylation of nitriles via borrowing hydrogen strategy with alcohol as alkylation agent, has been developed as one of the most attractive and atom-economic transformation, with only water as a byproduct. [5,6] Since 1981, when Grigg and co-workers first used RuH 2 (PPh 3 ) 4 as a catalyst in the alkylation of nitriles with alcohol, [7] a lot of effort has been devoted to exploring various catalysts, including Ru, [8][9][10][11][12][13][14][15] Rh, [16,17] Ir, [18][19][20][21][22] Pd, [23] Os, [24] Fe, [25] and Mn [26] . Of these, Ru complexes are the most reported, for example Gunanathan's group reported that Ru(PNP) (PNP = bis(2-(diphenylphosphino)-ethyl)amine) pincer complex showed good activity for α-alkylated reaction of arylmethyl nitriles.…”
Section: Introductionmentioning
confidence: 99%
“…In the Supporting Information of the original article, 1 spectra for 1 , 3 , trans‐ 4 , cis‐ 4 ′, 5a , 5c , 7 , 10 , 11 , 12 , 13 , 15 and trans‐ 16 were found to have been edited to remove solvents and impurities. Original products were located and the spectra were recorded and have been replaced for 1 , 5a , 5c , 7 , 10 , 11 and 15 .…”
mentioning
confidence: 99%